I.iv.2. Correspondence of John Pitt Kennedy concerning Ireland's difficulties, - Kennedy, John Pitt, 1796-1879 (1835)
MS 49,529 /24 Folder 1 : John Pitt Kennedy's correspondence concerning Irish affairs, 1835-1846. Correspondents include William Atkinson; the Reverand James Carlisle; A. Clendenning; Captain Henry James; Lord Larcom; Acheson Lyle; Timothy McNamara; William Smith O'Brien, John Abel Smith, James Wharton and John Wilson. Also includes correspondence with the Relief Commission, Board of Public Works, Commision for National Education and the Poor Law Commission. [22 items].